Strategi Pembinaan Aktivitas Keagamaan Siswa di Madrasah Aliyah Negeri Insan Cendekia (MAN-IC) Kabupaten Paser - Amirullah Amirullah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
As an attempt to create a balance between intellectual and spiritual quotients among students, the ministry of religious affairs of Indonesia has initiated a flagship program of Madrasah Aliyah (MA) Unggulan applying boarding school system for all the students. This paper, thus, aims at understanding the strategy of religious coaching at state-funded MA Insan Cendekia in Paser Regency as one of the Indonesian Ministry of Religious Affairs’ pilot program. This paper utilizes qualitative approach in analyzing data acquired through in-depth interviews with teachers and administrators at the school (MAN Insan Cendekia Paser). Findings reveal that the strategy of religious coaching applied by the school is the manifestation of its motto; performance, autonomy, and Islamic piety. The motto is translated into inspirational teacher program aimed at constructing students’ autonomy through religious, organizational, and instructional programs.Keywords: coaching strategy, madrassa students, and religious coaching.